Statistical modelling of determinants of child stunting using secondary data and Bayesian networks: A UKRI Global Challenges Research Fund (GCRF) action against stunting hub protocol paper - Rosenstock, Todd S.; Yet, Barbaros (BMJ, 2024)
Several factors have been implicated in child stunting, but the precise determinants, mechanisms of action and causal pathways remain poorly understood. The objective of this study is to explore causal relationships between the various determinants of child stunting.